CLIMATE CHANGE AND ECOLOGICAL CRISIS - Xudoyberdiyeva Dildora Baxodirovna (The Conference Hub, 2025)
Climate change is an urgent and complex global issue with far-reaching consequences for the planet’s natural systems, human well-being, and economic stability. It is primarily driven by anthropogenic factors such as greenhouse gas emissions, deforestation, and industrial expansion. The ecological crisis, which includes biodiversity loss, habitat destruction, and environmental pollution, is intricately linked with climate change and amplifies its effects. This article provides a comprehensive overview of the major causes of climate change, the ecological disruptions it causes, and the potential strategies for mitigation and adaptation. A multidisciplinary and cooperative approach is necessary to address these intertwined challenges and safeguard the future of life on Earth.
Keywords: Climate change, ecological crisis, greenhouse gases, biodiversity loss, sustainability, global warming, environmental degradation